Changing the Culture of Pediatric Palliative Care at the Bedside. Issue 1 (February 2021) - Drach, Laura L.; Cook, Michelle; Shields, Susan; Burger, Kristina J.
Abstract : The benefits of palliative care services have been widely documented; however, many organizations are unable to financially support the number of professionals needed to meet the growing demand. Nurses receive minimal training in palliative care, and the resulting knowledge gap can lead to a lack of confidence when providing the essential aspects of palliative care. Recognizing the needs of patients and staff, one organization created a Palliative Care Champions Program to support and educate bedside staff. The Champions received initial and ongoing education, allowing them to function as liaisons to the Palliative Care Team while providing education and mentorship to staff. A program evaluation tool measuring Champion comfort and confidence in the provision of palliative care has shown positive results. Champions reported an increase in confidence in their ability to identify appropriate consults and mentor staff, as well as an increase in comfort in being considered an expert in palliative care. Consults to the Palliative Care service increased by 28% within the first 12 months of program implementation. The Palliative Care Champions Program framework can be easily adapted to fit the needs of other organizations.